1990
DOI: 10.1172/jci114666
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for carrier-mediated transport of glutathione across the blood-brain barrier in the rat.

Abstract: Information on the origin of brain glutathione and the possibility of its transport from blood to brain is limited. We found a substantial uptake of f3Slabeled glutathione by the rat brain using the carotid artery injection technique. The brain uptake index of glutathione with and without an irreversible gammaglutamyl transpeptidase inhibitor, acivicin, was similar. No sign t differences in the regional uptake of labeled giutathione were found in rats pretreated with acivicin. The brain uptake index of tracer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(97 citation statements)
references
References 35 publications
4
92
1
Order By: Relevance
“…Mouse studies have shown that NAC completely crosses the capillary wall to enter brain tissue and extracellular space, and that the amount of NAC transported across the BBB is well within the therapeutic range of CNS-active agents (Farr et al, 2003). Also, an increase of plasma GSH should increase brain GSH since the tripeptide also crosses the BBB, possibly by Na + -dependent GSH transport (Kannan et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse studies have shown that NAC completely crosses the capillary wall to enter brain tissue and extracellular space, and that the amount of NAC transported across the BBB is well within the therapeutic range of CNS-active agents (Farr et al, 2003). Also, an increase of plasma GSH should increase brain GSH since the tripeptide also crosses the BBB, possibly by Na + -dependent GSH transport (Kannan et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings Brain uptake of glutathione, a tripeptide, measured by the BUI method showed saturation with a Km value of 5.8 mM, and is specific for the reduced form of glutathione, GSH. 81,82 Significant transport of GSH in intact form was also demonstrated by the brain perfusion method. 83 When mRNA obtained from brain capillaries was injected into oocytes, GSH transport activity, via both sodium-dependent and -independent mechanisms, was observed with a Km for sodium-dependent transport of 0.4 mM, demonstrating that the transporter protein is present at the BBB.…”
Section: Peptidesmentioning
confidence: 97%
“…There is a carrier mediated transport of GSH across the BBB (Kannan et al 1990), but it is found to be of low capacity (Cornford et al 1978). Indeed, brain extraction of radiolabeled GSH after intracarotid injection was only 0.5% (Cornford et al 1978).…”
Section: Discussionmentioning
confidence: 99%